Investigation of basalt/kevlar fiber-reinforced porcelain filler infused epoxy composite: A viable alternative for marine applications - Prem Anandh. A; P. Sivabalan; Vinayagam Mohanavel; Thandavamoorthy Raja (Results in Engineering)
This study investigates the mechanical properties, water absorption capacity, fatigue strength, and microstructural characteristics of a hybrid composite reinforced with basalt and Kevlar fibers and porcelain fillers blended epoxy matrix, designed for marine applications. The composite was fabricated using a hand lay-up technique was used to achieve a uniform distribution of fibers and fillers. Mechanical testing revealed significant improvements in tensile strength (217.64 MPa), flexural strength (223.62 MPa), and impact strength (39 J), particularly with the addition of 15 g of porcelain fillers, compared to pure polymer matrices. The presence of porcelain fillers enhanced the interfacial bonding between the fibers and matrix, leading to a synergistic reinforcement effect that improved the composite's mechanical properties. Water absorption tests indicated minimal moisture uptake (0.6 %) after 48 h of immersion in saltwater, demonstrating excellent resistance to water, a critical property for marine environments. Fatigue testing under 30,000 cyclic loading cycles revealed that the composite retained 55 % of its initial tensile strength, indicating high durability under fluctuating loads. The SEM and EDX analyses were conducted to examine the microstructural characteristics of the composite. SEM results showed improved interfacial bonding and minimal porosity, while EDX confirmed the presence of porcelain fillers, which contribute to the composite's enhanced stability and strength. These findings suggest that the incorporation of porcelain fillers into a basalt/Kevlar hybrid matrix results in a composite with superior mechanical properties, low water absorption, and excellent fatigue resistance, making it a potential material for marine applications.